PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI MODERASI - Astari, Yola; Rinofah, Risal; Mujino, Mujino (2019)
This study aimed to examine the effect of capital structure and profitability on firm value with company size as moderating varaible (Study of Property and Real Estate Companies listed on the Indonesia Stock Exchange (BEI) in the period 2014 – 2018). The population in this research is Property and Real Companies Estates listed on the Indonesia Stock Exchange (IDX) in the period 2014 - 2018. This study used 15 companies using purposive sampling method. This research’s technique used descriptive statistical tests, classical assumption tests, multiple linear regression analysis, moderated regression analysis (MRA). The results showed that the capital structure has a negative and not significant effect on firm value, positive and significant profitability on firm value, positive and insignificant size of the company, firm size is not able to moderate the effect on the structure of the firm's value. In fact, profitability is not able to moderate the effect of capital structure on firm value